You are on page 1of 9

A Further Note on Expanding Functions into Infinite Compositions: Imagery

John Gill

August 2014

Abstract: A heuristic note that further explores expansions of continuous complex functions into infinite
compositions. A continuation of A Note on Expanding Functions into Infinite Compositions 1 [1].

Infinite compositions of complex functions may occur in two forms:


n

I Inner or right compositions:

R tk (z ) = t1  t2    tn (z ) , T (z ) = lim R tk (z ) .
n

k =1

k =1

II Outer or left compositions:

Ltk (z ) = tn  tn 1    t1 (z ) , T (z ) = lim Ltk (z ) .


n

k =1

k =1

Convergence theory of each of these is discussed in [1]. Here, the emphasis will be on
converting certain functions into infinite expansions. Figures are simple topographic images.

---------------------------------------Consider functions
(1)

F ( z ) = z + a2z 2 + a3z 3 + , z < R

( R could be infinite)

A subclass of these functions can be described as functional equations of the following form:
(2)

F (nz ) = nF ( z ) + F m ( z ), n 2, m 2

Using the procedure described in [1]


(3)

zm
z
Fp ( z ) = R z + k ( m1)+1 and z p = npF p z
k =1
n
n

F ( z ) Fp ( zp )

As one possibility, the following can be used to show uniform convergence on compact subsets
of C : Write
(4)

fk ( z ) = z +

zm
nk ( m1)+1

, and Fj ( z ) = f1  f2  f j ( z )

--------------------------------------------------------------------------------------------------------------------Theorem 1 (Gill, 2011) Suppose f k ( z ) = z (1 + k ( z )) , with k analytic for z R1 and

k ( z ) < k ,

< . Choose 0 < r < R1 , and define R = R(r ) =

R1 r

. Then

(1 + )
k

k =1

Fj (z) = f1  f2  f j (z) G(z) uniformly for z R and

G '( z ) (1 + k ) < , k =
k =1

R1
k
r

-----------------------------------------------------------------------------------------------------------------------------------

Does G( z ) = F ( z )

Uniform convergence and continuity arguments applied to

F ( z ) G( z ) Fp ( z p ) G( z p ) + G( z p ) G( z )
show that, indeed, F ( z ) = G( z ) for a region containing the origin (we leave this vague).
Example 1: F (3z ) = 3F ( z ) + 2F 2( z )


z2
F ( z ) = R z + 2 k +1 , -20<x,y<20 n=20
k =1
3

Example 2:


z3
F (2z ) = 2F ( z ) + F 3( z ) F ( z ) = R z + 2k +1 ,
k =1
2

-40<x,y<40

n=20

Restricting
F (nz ) = nF ( z ) + F 2( z )

(5)
We find that

(6) f k ( z ) = z + n,k z 2

where n,k =

nk +1

And
(7)

gk ( z ) = f k1 ( z ) =

1
1 + 4 n ,k z 1
2

, (principle root) leading to

n ,k

(8) F 1( z ) = G( z ) = lim Gn( z ) , Gn( z ) = n  gn  gn1  g1( z ) and n z


n

Convergence of the inverse composition can be determined, for example, by the following
theorem:

-------------------------------------------------------------------------------------------------------------------------------------Theorem 2 (Gill, 2011) Let {g n } be a sequence of complex functions defined on S=(|z|<M) . Suppose

there exists a sequence { n } such that

< and g n (z) z < Cn if z < M . Set

k=1

= C k and R 0 = M > 0 . Then, for every z S0 = ( z < R 0 ) ,


1

G n (z) = g n  g n 1  g1 (z) G(z) , uniformly on compact subsets of S0 .


---------------------------------------------------------------------------------------------------------------------------------------

Example 3:

F(z)

F ( z ): F (3z ) = 3F ( z ) + (1 + i )F 2 ( z ) , F 1 ( z ) = G( z ) -20<x,y<20

G(z)

n=20

Now consider
(9)

F (nz ) = nF ( z ) + T ( z ) F m ( z ), n 2, m 2 and T ( z ) F m( z ) = 2z 2 + 3z 3 + ,

which gives
m

z0 z
Fp ( z0 ) = R z + T k k ( m1)+1  z0
k =1
n n

(10)

z3
Example 4: F (2z ) = 2F ( z ) + z F 3( z ) Fp ( z0 ) = R z + z0 3k +1  z0
k =1
2

-40<x,y<40 n=20

z0

z3
k
Example 5: F (2z ) = 2F ( z ) + e z F 3( z ) F ( z0 ) = R z + e 2 k +1  z0 , -40<x,y<40 n=20
k =1
2

z 0 2 z 2
Example 6: F (3z ) = 3F ( z ) + z F ( z ) Fp ( z0 ) = R z + k k +1  z0 , -45<x,y<45 n=30
k =1
3 3
2

Example 7: F (2z ) = 2F ( z ) +

z3
z3
Fp ( z0 ) = R z + k0  z0
k =1
F( z )
4 z

-50<x,y<50 n=20


z2
Example 8: F (2iz ) = 2iF ( z ) + F 2( z ) F ( z ) = R z +
k +1
k =1
(2i )

F( z ) z

F(z)

-20<x<70

, -40<y<40

-40<x,y<40 n=30

Example 9:


z3
F (2iz ) = 2iF ( z ) + F 3( z ) F ( z ) = R z +
2k +1
k =1
(2i )

z

z2
k
Example 10: F (3z ) = 3F ( z ) + z 2e F ( z ) F ( z0 ) = R z + k0+1 e 3  z0
k =1
3

-40<x,y<40 n=30

-20<x,y<20 n=20

Example 11: F (2z ) =

2z
z0
F ( z0 ) = R
 z0
k
k =1 1 z / 2
1 F(z )

-50<x<80, -50<y<50 n=30.

z
z
z
z
8
2
4
Another way to look at this expansion is as a continued fraction: F ( z ) =
1 1 1 1

Example 12: F (2z ) =

z + F(z )
1 + F( z )

z0 + z
F ( z0 ) = R
 z0
k =1 2 + z / 2k 1

-70<x<40 , -40<y<40 n=30

[1] J. Gill, A Note on Expanding Functions into Infinite Compositions, Comm Anal Th Cont Frac, Vol XX (2014)